Enhanced photocatalytic performance of magnetite/TS-1 thin film for phenol degradation - Hsiu-Ling Hsu; L. Selva Roselin; R. Savidha; Rosilda Selvin (Journal of Saudi Chemical Society)
Photocatalytic degradation method is an emerging technique for complete removal of pollutants. Several semiconductor photocatalysts are reported as photocatalysts for industrial wastewater treatment in environmental applications. In this study Magnetite/TS-1 composite materials was used for photocatalytic degradation of phenol. Magnetite nanoparticles (MNP) (10 wt%) were dispersed with nanocrystalline Titanium Silicate-1 zeolite (TS-1). The Magnetite/TS-1 composite materials were characterized with various techniques. The structural analysis reveals the presence of MNP and zeolite-MFI phases in Magnetite/TS-1 composite materials. The average particles size of the magnetite nanoparticles is less than 5 nm and that of the composite nanoparticles are in the range of about 90 nm with micropore volume 0.110 cm3/g and the external surface area 120 m2/g. The photocatalytic experiments were carried out in a thin film flow photoreactor under UV radiation. The results showed that Magnetite/TS-1 composite materials exhibited improved activity for the degradation of phenol compared to TS-1. Preliminary studies proves that aeration is necessary for the photocatalytic reaction. The reaction parameters such as flow rate, pH and phenol concentration are optimized as 8 ml/min, pH 7.0 and 75 mg/L respectively. To understand the active species involved in the degradation of phenol radical scavengers such as NaI, benzoquinone and isopropyl alcohol are used to trap hole (h+), superoxide anion radical and hydroxyl radical (OH), respectively. From the obtained results it is envisaged that hydroxyl radicals are predominantly involved in complete oxidation of phenol. The extent of degradation of phenol was determined by measuring the amount of CO2 formed in the reaction. The results confirms that 99.6 % carbon in phenol is converted to CO2.